2016
DOI: 10.1016/j.acra.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Osteochondritis Dissecans

Abstract: In this paper, we utilize arthroscopy as the gold standard to determine if MRI can predict OCD lesion stability, the most important information to guide patient treatment decisions. To our surprise, the analysis of the existing radiology reports that addressed stability revealed an overall accuracy in defining OCD lesion stability of about 53%. The classification system of the ICRS, created by an international multidisciplinary, multi-expert consortium, did markedly improve the accuracy, but consistency among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…determined the agreement for the Dipaola/Nelson classification based on MRs of knee OCD. 32 The authors reported moderate agreement among two musculoskeletal-trained radiologists and one musculoskeletal radiology fellow, compared to slight agreement in our investigation concerning capitellar OCD. Higher reliability reported by the authors may be due to the fact that the Dipaola/Nelson classification was originally developed for knee and talar OCD.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…determined the agreement for the Dipaola/Nelson classification based on MRs of knee OCD. 32 The authors reported moderate agreement among two musculoskeletal-trained radiologists and one musculoskeletal radiology fellow, compared to slight agreement in our investigation concerning capitellar OCD. Higher reliability reported by the authors may be due to the fact that the Dipaola/Nelson classification was originally developed for knee and talar OCD.…”
Section: Discussionsupporting
confidence: 48%
“…The interobserver reliability for existing classification systems was lower in our investigation compared to two previous studies. 7 , 32 Itsubo et al. reported an intraclass coefficient, of their own developed classification, that ranged from 0.82 to 0.88 (i.e.…”
Section: Discussionmentioning
confidence: 99%
“… 9 This system divides OCLs on MRI into 4 categories: grade 1, thickening of the cartilage without disruption, including bone marrow edema or fluid at the bone-lesion interface; grade 2, cartilage breached and fluid at partial but not entire interface; grade 3, cartilage completely disrupted with fluid interface surrounding lesion; and grade 4, displaced fragment. 12 …”
Section: Methodsmentioning
confidence: 99%
“…Commonly found in the knee, plain radiographs are used reliably for diagnosis, staging [ 2 ], and management. Advanced imaging, such as MRI, is often used in conjunction with radiographs and physical exam for staging and surgical planning though inconsistencies in protocols and findings limit its clinical utility [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%